2017
DOI: 10.1002/jsfa.8604
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the proximate, fibre, mineral content, amino acid and the fatty acid profile of Marula (Sclerocarya birreacaffra) nut and soyabean (Glycine max) meals

Abstract: The low crude protein content in MNMs compared to SBM is comparable with other conventional dietary protein sources. Thus, the MNMs could be used as protein and energy feed ingredients. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…The extent of fatty acid content of the meat has been associated with the composition of the diet ( Raes et al., 2004 ). Partially defatted MNM contains high content oleic acid (76.08 to 77.81%), palmitic acid (12.36 to 14.16%) and linoleic acid (7.15 to 7.20%) ( Malebana et al., 2018 ) and the hexane-extracted MNM used in the current study contained 65.93% oleic acid, 14.16% palmitic acid and 6.68% linoleic acid. The breast meat from Japanese quail is reported to contain 34.13 to 34.65% total saturated fatty acids (TSFA), 40.70 to 49.70% total monounsaturated fatty acids (TMUFA) and 13.81 to 24.98% total polyunsaturated fatty acids (TPUFA) ( Gecgel et al., 2015 ; Genchev et al., 2008 ).…”
Section: Discussionmentioning
confidence: 93%
“…The extent of fatty acid content of the meat has been associated with the composition of the diet ( Raes et al., 2004 ). Partially defatted MNM contains high content oleic acid (76.08 to 77.81%), palmitic acid (12.36 to 14.16%) and linoleic acid (7.15 to 7.20%) ( Malebana et al., 2018 ) and the hexane-extracted MNM used in the current study contained 65.93% oleic acid, 14.16% palmitic acid and 6.68% linoleic acid. The breast meat from Japanese quail is reported to contain 34.13 to 34.65% total saturated fatty acids (TSFA), 40.70 to 49.70% total monounsaturated fatty acids (TMUFA) and 13.81 to 24.98% total polyunsaturated fatty acids (TPUFA) ( Gecgel et al., 2015 ; Genchev et al., 2008 ).…”
Section: Discussionmentioning
confidence: 93%
“…Rich) nut cake (ANC) is a by-product that is derived from oil extraction of the dry seeds of ripe amarula fruit, an indigenous fruit tree that is widely distributed throughout the Sub-Saharan Africa (Mthiyane and Mhlanga, 2017). Research has shown that ANC contains crude protein (CP) that ranges from 325 to 470 g/kg dry matter (DM) (Mthiyane and Mhlanga, 2017, Malebana et al, 2018, Nkosi et al, 2019, comparable to that of SBM, but higher than that of other conventional protein sources such as canola seed meal (270 g CP/kg DM, NRC, 2001). The ANC contains ether extract (EE) that ranges from 344 to 498 g EE/kg DM (Mthiyane and Mhlanga, 2017, Malebana et al, 2018, Nkosi et al, 2019, which depends on the processing method for oil extraction (Malebana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that ANC contains crude protein (CP) that ranges from 325 to 470 g/kg dry matter (DM) (Mthiyane and Mhlanga, 2017, Malebana et al, 2018, Nkosi et al, 2019, comparable to that of SBM, but higher than that of other conventional protein sources such as canola seed meal (270 g CP/kg DM, NRC, 2001). The ANC contains ether extract (EE) that ranges from 344 to 498 g EE/kg DM (Mthiyane and Mhlanga, 2017, Malebana et al, 2018, Nkosi et al, 2019, which depends on the processing method for oil extraction (Malebana et al, 2018). The high fat content in ANC could provide su cient energy in diets and allow pigs to improve feed e ciency, daily gains and thus increase muscle accretion (De la Llata et al, 2001, Stephenson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The main reaction reagents include various kinds of quinolines [31–34], aromatic amines, aliphatic amines, H‐phosphite (diphenylphosphite, dibenzylphosphite), and so forth, all of which are commercially available by Aladdin, and all of which are produced by Anarchic Reagent or Bailingwei Reagent Company; Diethyl h‐phosphite and di‐isopropyl H‐phosphite were both prepared by the method reported in the previous literature. All the solvents used are the 500 mL bottled reagent of Romeo.…”
Section: Resultsmentioning
confidence: 99%